Belis Gading dalam Perkawinan Adat Lamaholot Desa Leworaja: Telaah Normatif Empiris dalam Perspektif Hukum Islam - Insafiyah Lamablawa, Nurmata; Fakhrurazi, Fakhrurazi; Alfarisi, Usman; Zakaria, Endang; Nurhadi , Nurhadi; Fatmakartika, Rini; Yumna, Laila (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2023)
This study examines the practice of ivory belis in Lamaholot traditional marriage in Leworaja Village, Lembata Regency, East Nusa Tenggara. Belis in the form of elephant ivory is a customary requirement that has social, cultural, and honorary values for Lamaholot women. However, this practice often burdens men economically and raises normative issues in the perspective of Islamic law which emphasizes the simplicity of dowry and the prohibition of burdening prospective husbands. This research uses a qualitative method with data collection techniques through in-depth interviews with traditional leaders, religious leaders, and local communities, as well as analysis of customary law documents and marriage fiqh. The results of the study show that ivory belis is seen as a symbol of self-esteem and kinship bonds, but in Islamic law this tradition cannot be positioned as a legal condition for marriage. Islam only requires a simple dowry which is the full right of the wife. Therefore, the practice of ivory belis requires reinterpretation in order to maintain the cultural values of the Lamaholot community while being in line with the principles of maqaṣid al-shari'ah which emphasizes convenience, justice, and benefits.